2016
DOI: 10.1080/17437199.2016.1219672
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of health locus of control with specific health behaviours and global health appraisal: a meta-analysis and effects of moderators

Abstract: Health locus of control (HLOC) refers to beliefs regarding how one’s health is influenced by oneself, others, or fate. This meta-analysis investigated whether three HLOC dimensions (internality/I-HLOC, powerful others/P-HLOC, chance/C-HLOC) were related to both specific health behaviours and global health appraisal, and whether these relationships were moderated by gender and age compositions, individualism, and power distance. Three-level mixed-effects meta-analysis was performed on studies examining the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 57 publications
5
62
0
2
Order By: Relevance
“…For example, the present findings are consistent with a study comprised of a nationally representative German sample in which adults who scored higher on the internal HLOC scale reported engaging in more healthrelated behaviors (Grotz, Hapke, Lampert, & Baumeister, 2011). Moreover, a metaanalysis of 76 studies with adults-some of which were crosssectional-showed that stronger internal HLOC orientations were associated with two health promoting behaviors, specifically exercise and diet (Cheng, Cheung, & Lo, 2016). Interestingly, internal HLOC orientations were not significantly associated with healthcompromising behaviors such as smoking or drinking alcohol (Cheng et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For example, the present findings are consistent with a study comprised of a nationally representative German sample in which adults who scored higher on the internal HLOC scale reported engaging in more healthrelated behaviors (Grotz, Hapke, Lampert, & Baumeister, 2011). Moreover, a metaanalysis of 76 studies with adults-some of which were crosssectional-showed that stronger internal HLOC orientations were associated with two health promoting behaviors, specifically exercise and diet (Cheng, Cheung, & Lo, 2016). Interestingly, internal HLOC orientations were not significantly associated with healthcompromising behaviors such as smoking or drinking alcohol (Cheng et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, internal HLOC orientations were not significantly associated with healthcompromising behaviors such as smoking or drinking alcohol (Cheng et al, 2016). In addition, internal HLOC orientations were associated with mental and physical quality of life, as well as lower levels of anxiety and depres sion (Cheng et al, 2016). Although this previous research supports associations between HLOC and better health, it speaks solely to the correlational relationship between HLOC and health.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…On an individual level, the manner in which our participants resist an aging body, and the control they attempt to assert over various physical and social barriers, may be an effective and empowering way to approach their lives. Much of the literature in psychology suggests that locus of control (i.e., beliefs regarding whether one's health is controlled by oneself, others, or fate) is an important predictor of mental health and well-being, as well as proactive behaviour (Cheng, Cheung & Lo, 2016;Cobb-Clark, Cassenboemher & Schurer, 2014;Norman, Bennett, Smith, & Murphy, 1997). From a societal perspective, however, this focus on individual agency is problematic, for it assumes that everyone, irrespective of health condition or economic circumstance, can exert similar control over the aging process (Gard et al, 2017;Gard & Dionigi, 2016).…”
Section: Discussionmentioning
confidence: 99%
“… 24 27 A recent meta-analysis of 76 independent studies illustrated the relevance of HLoC on a broad range of health outcomes and health behaviors. 28 Furthermore, specific research evidence on HLoC and pain conditions has shown that HLoC constructs of Internality (ie, low) and Externality (ie, high) are associated with higher pain intensity, increased psychological morbidity in those with pain, 29 , 30 and can influence an individual’s response to treatment. 31 , 32 At present, pain research has considered HLoC as a covariate factor (ie, mediator explaining a relationship between pain and another variable, or associating with outcomes for those with pain), often focused on response to treatment.…”
Section: Introductionmentioning
confidence: 99%